Mitosis dan Ritual Mohon Air Hujan di Kawasan Pura Batukaru Kabupaten Tabanan-Bali: Perspektif Ekologi Budaya - I Nyoman Wardi (Bumi Lestari Journal of Environment, 2023)
Batukaru Temple Cultural Reserve is one of the Kahyangan Jagat (State Temple) in Bali, and its area has been designated by UNESCO (2012) as one of the World Cultural Heritage of Bali. This study aims to reveal the meaning of the ritual of asking for rainwater (pakelem ritual) for traditional farming communities (subak) in the Batukaru Cultural Heritage Area of Tabanan Regency. The study was conducted by collecting data through observation, interviews, and literature study. The collected data were analyzed descriptively qualitatively using the cultural ecology approach. Successively, sacrificial rituals and offerings (mapag/mendak toya rituals) are performed every year. In the pakelem/pangeleb ritual at Lake Tamblingan, the sacrificial means offered is sudamala buffalo (kebo ius merana). The implementation of the mendak toya and pakelem rituals every year in different places implicitly represents the knowledge of farming communities (subak) related to natural ecosystems that are interdependent, namely in particular water ecosystems related to climate (rainfall), mountain and forest ecosystems (wana-giri), watersheds and lake ecosystems. Implicitly these rituals reflect the awareness of the farming community (Subak) on the importance of water resources for agricultural life and other interests.